An Analysis on Students’ Difficulties in Translating Business Text - Saswandi, Tri (JR-ELT (Journal of Research in English Language Teaching), 2017)
This research attempts to find out students’ difficulties, their translation quality and the causes of such difficulties in translating business text. The type of this research is a descriptive research. The research data were obtained from translation test and the analysis of students’ translations. The result showed that the students have difficulties in the level of lexical, grammatical, contextual, textual and cultural problems. It was employed two raters from English lecturers to assess the test and describe the students’ translation quality objectively and two lecturers of Bahasa to validate the target language. The result also showed that the qualities of students’ translation were classified into bad quality. The analysis of students’ translation moreover showed that the causes of students’ difficulties were lack of translation competencies; lack of language competence, textual competence, subject competence, cultural competence and transfer competence. Dealing with text in certain discipline especially business text, it should be separately instructed in teaching learning process or the text should be analyzed and comprehended by students before going to transfer the whole message into target text. Also, translation process and strategies should be taught in the same time with the practice of translation.